2020
DOI: 10.3390/children7100153
|View full text |Cite
|
Sign up to set email alerts
|

Nebulizer Care and Inhalation Technique in Children with Cystic Fibrosis

Abstract: Nebulizers are used by the great majority of cystic fibrosis patients for delivery of cornerstone treatments. Inhalation technique and adequate disinfection and maintenance are important for optimizing medication delivery. In this study, inhalation technique and nebulizer disinfection/maintenance were assessed in cystic fibrosis patients by direct observation in clinic and completion of a scoring sheet. A total of 108 patients were recruited. The maximum inhalation technique score was attained by 30.5% and ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Following diagnosis, caregivers, who are usually a parent or close family member, are required to carry out or assist with daily treatments, such as physiotherapy to clear static mucus from the respiratory tract 4 and the administration of nebulized treatments, along with many other different medications to treat and prevent organ damage. 5 These therapies are intended to alleviate symptoms and reduce the severity of respiratory events, such as exacerbations and infections, 6 but are time-consuming. Children with CF spend an average of 75 min/day receiving treatment, 7 which must be performed by caregivers in addition to other familial and occupational commitments.…”
Section: Introductionmentioning
confidence: 99%
“…Following diagnosis, caregivers, who are usually a parent or close family member, are required to carry out or assist with daily treatments, such as physiotherapy to clear static mucus from the respiratory tract 4 and the administration of nebulized treatments, along with many other different medications to treat and prevent organ damage. 5 These therapies are intended to alleviate symptoms and reduce the severity of respiratory events, such as exacerbations and infections, 6 but are time-consuming. Children with CF spend an average of 75 min/day receiving treatment, 7 which must be performed by caregivers in addition to other familial and occupational commitments.…”
Section: Introductionmentioning
confidence: 99%
“…Current study showed that 80% of the patients were using their nebulizers longer than the recommended time period. Prolonged use of the nebulizer can cause fissures on the surface which makes cleaning and disinfection process less effective and increase the risk of contamination 19,30 . In addition, it is also important to replace the nebulizer every 6 months per manufacturer recommendations because the nebulizer parts begin to wear down and that impacts particle size which will cause a reduction in medication dose administered.…”
Section: Discussionmentioning
confidence: 99%